Production, Characterization, and Application of Bacillus licheniformis W16 Biosurfactant in Enhancing Oil Recovery - Joshi, Sanket J.; Al-Wahaibi, Yahya M.; Al-Bahry, Saif N.; Elshafie, Abdulkadir E.; Al-Bemani, Ali S.; Al-Bahri, Asma; Al-Mandhari, Musallam S. (Frontiers in Microbiology, 2016)
The biosurfactant production by Bacillus licheniformis W16 and evaluation of biosurfactant based enhanced oil recovery using core-flood under reservoir conditions were investigated. Previously reported nine different production media were screened for biosurfactant production, and two were further optimized with different carbon sources (glucose, sucrose, starch, cane molasses or date molasses), as well as the strain was screened for biosurfactant production during the growth in different media. The biosurfactant reduced the surface tension and interfacial tension to 24.33+0.57mN m-1 and 2.47+0.32mN m-1 respectively within 72h, at 40 C, and also altered the wettability of a hydrophobic surface by changing the contact angle from 55.67°+1.6° to 19.54°+0.96°. The critical micelle dilution values of 4X were observed. The biosurfactants were characterized by different analytical techniques and identified as lipopeptide, similar to lichenysin-A. The biosurfactant was stable over wide range of extreme environmental conditions. The core flood experiments showed that the biosurfactant was able to enhance the oil recovery by 24-26% over residual oil saturation (Sor). The results highlight the potential application of lipopeptide biosurfactant in wettability alteration and microbial enhanced oil recovery processes.